Progress and challenges in HTL-free pervoskite solar cells - Revathy Raghunathan Lekshmy (22046402) (2025)
HTL-free PSCs are among the most cutting-edge and quickly developing technologies in the solar energy industry due to their easier fabrication processes and cheaper production costs. However, instability at the interfaces is one of the several challenges that need to be sorted out for the full understanding of HTL-free PSCs for regard to successful commercialization. Thus, this review emphasizes the recent advancements and challenges in the development of HTL-free PSCs. Reducing surface and grain boundary defects and enhancing the quality of perovskite thin films are two important ways to enhance device performance. Additionally, a thorough comprehension on improving long-term stability using mixed and all-inorganic perovskites, as well as surface passivation techniques. Furthermore, an introduction of graded junctions within the perovskite film is presented to demonstrate potential for further performance enhancement. The review also elucidates that despite the simplicity of the HTL-free structure, comprehensive engineering of various components is crucial for the advancement of HTL-free PSCs. In summary, continued innovation and integration of advanced techniques, HTL-free PSCs are poised to become competitive in the photovoltaic market, combining high efficiency with long-term stability. Other Information Published in: Solar Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.solener.2025.113831